Populus D-type cyclin gene PsnCYCD1;1 accelerates cell division and participates in secondary growth of vascular bundles - Zheng, Tangchun (Journal of experimental botany, 2023)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.